(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Evaluate the the pain-relieving effects of electro-acupuncture combined with ultrasound therapy in patients with periarthritis humeroscapularis at National Hospital of Traditional Medicine. Method: Clinical intervention study, comparing before - after of treatment on 50 patients with a confirmed diagnosis of periarthritis humeroscapularis, treated with electro-acupuncture combined with ultrasound therapy. Results: After 20 days of treatment, the average VAS score decreased from 5.58 ± 0.94 points to 1.74 ± 0.62 points; the SPADI pain score decreased from 58.44 ± 14.76 points before treatment to 21.39 ± 9.18 points on day 20, a reduction of 30.05 ± 12.17 points. Total SPADI score decreased from 51.22 ± 8.47 points before treatment to 16.75 ± 6.39 points, a decrease of 34.47 ± 7.29 points. Most patients have good and fair general treatment effectiveness, accounting for 44% and 50% respectively. There is a difference in the overall treatment effect before - after treatment with p < 0.05. Conclusions: Electro-acupuncture combined with ultrasound therapy is effective in treating periarthritis humeroscapularis.